The role of postharvest thyme oil-based alternatives on stimulated induction of defence mechanisms in avocados (Persea americana Mill.) for the control of anthracnose - Korsten, Lise (2026)
Thesis (PhD (Plant and Soil Sciences))--University of Pretoria, 2016.